Edukasi Pentingnya Memahami Kesehatan Reproduksi dan Napza pada Remaja di Rw 01 Desa Pasir Jambu Kabupaten Bogor - Triswanti Triswanti; Nurul Herawati; Siti Anisa Asyfari; Rina Lindayanti; Putri Anugrah Rahayu; Alya Zulfajriani; Wanda Latipah; Virizky Agustin Rambe; Sukma Fiftyasari (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Adolescents are an age group that is vulnerable to various health problems, including a lack of understanding about reproductive health and the dangers of narcotics (narcotics, psychotropics, and addictive substances). Lack of education in these two aspects can lead to risky behavior, such as premarital sex, unwanted pregnancy, sexually transmitted infections (STIs), and drug abuse which have negative impacts on physical, mental, and social health. This community service activity aims to provide education about reproductive health and the dangers of drugs to adolescents in RW 01 Sukaraja Village, Bogor Regency as a preventive measure in building awareness and healthy living behavior in adolescents. The method used in this program is an educational approach through interactive discussions, and counseling based on visual and digital media delivered to adolescent groups in schools and communities. Evaluation was carried out by comparing the level of understanding of participants before and after the activity through pre-test and post-test questionnaires. The evaluation results showed a significant increase in participants' understanding of the importance of maintaining reproductive health and avoiding drug abuse. In addition, participants showed high enthusiasm in the discussion and expressed readiness to apply the knowledge gained in everyday life. In conclusion, education on reproductive health and the dangers of narcotics is very important in forming healthy mindsets and behaviors among adolescents, especially adolescents in RW 01 Sukaraja Village, Bogor Regency. The sustainability of this education program needs to be supported by synergy between educators, health workers, parents, and the community so that the information provided can continue to be updated and implemented effectively